KEPADATAN POPULASI DAN POLA DISTRIBUSI BULU BABI (Diedema setosum) di PULAU ABANG BATAM - Efendi, Yarsi; Nurdiana, Juwita; Agustina, Fenny; Campina, Teny; Sefira, Anisa (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
This research aims to describe the population density of Sea Urchin (Diadema setosum) and it’s distribution pattern in the waters of Abang Island, Galang District, Batam City - Indonesia. Carried out in June 2023. Observations at 3 stations, using survey methods. Sampling was carried out using 3 line transects 20 meters long at each station, placing the transects from the shoreline towards the sea and placing observation plots 1m x 1m on the left and right of the transects. Measurement of water quality parameters; pH, salinity, depth, Dissolved Oxygen (DO), and temperature. The highest density was 2.28 ind/m2 found at station I with a number of 228 individuals and the lowest was 0.81 ind/m2 found at station II with a number of 81 individuals. The distribution pattern of sea urchins (Diadema setosum) was in clustered were found at all stations.